Beyond maximum density: multi-parameter insights into Scots pine climate sensitivity - Inga K. Homfeld; Frederick Reinig; Edurne Martinez del Castillo; Max C. A. Torbenson; Oliver Konter; Rob Wilson; Paul J. Krusic; Neil J. Loader; Hakan Grudd; Emily Reid; Kayleigh Letherbarrow; Jan Esper (Trees, 2025)
Key message Climate sensitivity of Pinus sylvestris has changed in minimum density while maximum density remains mostly stable, suggesting the use of additional density parameters could help detect response changes. Abstract As one of Eurasia's most widely distributed conifer species, Pinus sylvestris L. is frequently used in dendroclimatological reconstructions based on tree-ring width (TRW) and maximum latewood density (MXD). However, the climatic signals of additional parameters such as earlywood/latewood density (EWD/LWD) or minimum density (MND) are often overlooked, leaving their skill unexplored. Here, we investigate the growth responses of multiple P. sylvestris tree-ring parameters to ongoing climate change at two sites with contrasting climatic conditions using well-replicated density data from Scotland and Sweden. Correlations with mean, minimum, and maximum temperatures are strongest for LWD and MXD at both sites, with coefficients ranging from 0.5 to 0.7 for July, August, and the June–August season ( p < 0.05). A significant ( p < 0.05) negative correlation between MND and July temperatures was identified in the Swedish Torneträsk (TOR) data ( p < 0.05), which diminished since the late twentieth century. A comparable inverse MND temperature signal and change into the twenty-first century is not reflected in northern Scotland’s overall wetter and warmer site, suggesting a fundamental physiological change in tree-ring formation under global warming. A shift in the sensitivity of tree growth at northern European sites could reduce the effectiveness of proxies from such locations, posing implications for high-resolution climate reconstructions.